Potreba N. A. Тranslation interpretations of I. A. Bunin - Potreba N. A. (Philological Treatises, 2020)
The article is devoted to the problem of “interpretation” in the process of translation. A special attention is paid to the aspects of the literary text being created in the target language. Our research proves that literary text is characterized by a certain amount of interpretations, and that becomes evident while the peculiarities of the Bunins translation.